Menumbuhkan Jiwa Wirausaha Bagi Anak-Anak Di Distrik Warsa - Sarlota Arrang Ratang; Transna Putra Urip (UNIVERSITAS CENDERAWASIH, 2021)
The purpose of this activity is so that children in Warsa District, Biak Regency are able to understand and have an entrepreneurial spirit, be able to practice marketing (simple trading techniques) and promote the conditions of natural wealth in the surrounding environment The results of this training activity include, The achievement of training objectives, the achievement of the planned material targets and the ability of participants to understand the training material. The participants of this training were 25 children around the activity location. This figure shows that this training / socialization activity meets the target of participants reaching 95% and can be said to be successful / successful.